Availability Payment Based Public Private Partnerships In Indonesia - Syugiarto, Syugiarto (PARADIGMA : Jurnal Administrasi Publik, 2024)
This research aims to find out projects built in Indonesia using PPP with the Availability Payment scheme. This research itself uses qualitative research with a library study method. Qualitative research is a research scheme which uses observational, communicative and documentary methods in natural settings to understand the social world. Meanwhile, literature study is a form of structured investigation using certain methods, rules and techniques. The research results show that Availability Payment is one of the Indonesian government's options in infrastructure development. Three of the five PPP projects are in the payment stage to the private sector within the agreed time. Meanwhile, the PPP project for the drinking water supply system in West Semarang and the non-toll road preservation for the South Sumatra section are still in the study stage and are being tendered to private companies who wish to carry out the PPP project